Money mischief in the Eurozone: Reforming the European Monetary Union - Fredrik Erixon (European Centre for International Political Economy (ECIPE), 2013)
The European Central Bank has been a source of monetary disorder in the Eurozone. It was complicit in creating a huge asset bubble and growing current account imbalances in the Eurozone in the pre-crisis years. And it has been complicit in creating the drawn-out recession in the Eurozone in the past years. Its failure stems from a misguided monetary policy based on pure inflation targeting and a progressive downgrade of the role of money in monetary policy. For the ECB to become a source of macroeconomic stability, its policy, targets an operation of instruments should be changed. It does not mean that price stability should be ditched, or that a new mandate needs to be created. Yet it means that it should explore alternatives to the current monetary policy regime.
Keywords: 330